Rectal prolapse as the initial presentation of rectal cancer—A case report - Jurić, Oliver; Lisica Šikić, Nataša; Žufić, Vanja; Matak, Luka; Karlo, Robert; Mihanović, Jakov (Frontiers in Surgery, 2023)
Herein we report the case of a 63-year-old female tourist who presented to our Emergency Department with complete rectal prolapse. She had complained of diarrhea with traces of blood and mucus and had experienced fatigue after hiking. After the initial evaluation, it became clear that prolapse bares a large rectal tumor as a leading point. The prolapse was reduced under general anesthesia, along with a tumor biopsy. Further workup confirmed locally advanced adenocarcinoma of the rectum, which was treated with neoadjuvant chemoradiation followed by curative surgery in another hospital after repatriation. Rectal prolapse affects people of all ages, but it is more common in older adults, particularly women. Treatment options vary depending on the severity of the prolapse and can range from conservative measures to surgical interventions. This case report highlights the importance of early recognition and appropriate management of rectal prolapse in the emergency setting and the possibility of an underlying malignancy.